Economic complexity and greenhouse gas emissions - Romero, João P.; Gramkow, Camila (World development, 2021)
•Economic complexity contributes to reduce greenhouse gas emission intensity.•Production of complex goods is associated with lower emission intensities due to their cleaner manufacturing processes and high value-added.•Economic complexity contributes also to reduce greenhouse gas emissions per capita.•The Product Emission Intensity Index (PEII) proposed in the paper provides useful information for climate and green industrial policies.•The knowledge embedded in the productive structure of complex economies encompasses the knowledge required for cleaner production technologies. The contribution of the paper is twofold. First, it provides evidence that economic complexity contributes to reduce greenhouse gas emission intensity as well as per capita emissions. It is argued that the production of complex goods is associated with lower emission intensity due to the types of technologies used in the production of such goods and their high value-added characteristic. Using data for 67 countries between 1976 and 2012, the tests reported in the paper suggest that an increase of 0.1 in the economic complexity index generates a 2% decrease in next period’s emissions of kilotons of CO2e per billion dollars of output as well as in emissions per capita. Second, the paper proposes a Product Emission Intensity Index (PEII) associated with the production of 786 goods. The index is a weighted average of the emissions of the countries that export each given product with revealed comparative advantage. This index makes it possible to analyse specifically what products are associated with higher emission intensities, contributing to the formulation of policies aiming to reduce greenhouse gas emissions by shifting production away from high-emission intensity products as much as possible. The index corroborates that complex products are associated with lower emission intensities.